(3aQGFV TgGH GdOjfs - (3eMeO Hf CMeO Hf Ydj Hf CHj WGdH, TgGH GdOjf CHh MGeOs ((3GdLGeY GdYJjb GdTgjQ HGdMdHi s)
(3ChdgG (B:s
(3jHOC ef JQcI GdejJ HGdJLgjR hGdJcajf hbVGA GdOjhf hJfajP GdhUGjG s
(3BNQgG (B:s
(3jfJgi HHGH Phi GdCQMGe Chdge HGdejQGK ChdG HfGJ hChdGO HfGJ GdCHf s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGdKs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1250s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3aQGFV bhdg (B5) s
Keywords: (3Yde GdaQGFVs